(untitled) - Honig, Bonnie (Princeton, N.J., 2001)
This dilemma underlies age-old debates about immigration, citizenship, and national identity that are strikingly relevant today. In Democracy and the Foreigner, Bonnie Honig reverses the question: What problems might foreigners solve for us? Hers is not a conventional approach. Instead of lauding the achievements of individual foreigners, she probes a much larger issue--the symbolic politics of foreignness. In doing so she shows not only how our.
Keywords: Imperialism,International relations.,Chủ nghĩa đế quốc,Quan hệ quốc tế.